2007
DOI: 10.1002/chin.200745023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of a New Nanoporous‐Like Keggin Heteropolyanion Salt: K3(H2O)4 [H2SiVW11O40] (H2O)8+x.

Abstract: The nanoporous-like title compound is precipitated by addition of KCl to an aq. HCl solution of K8[SiW11O39] and NaVO3 and characterized by EDS, single crystal XRD, UV/Vis, IR, and Raman spectroscopy, and 1 H, 51 V, and 29 S solid state NMR spectroscopy. K3(H2O)4[H2SiVW11O40](H2O)8+x crystallizes in the hexagonal space group P62 with Z = 3 and contains large water-filled channels. A uniform distribution of vanadium over the 12 metal sites of the α-Keggin anion is observed. -(DE PAIVA FLORO BONFIM, R.; DE MOURA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The obtained bands agree with the ones reported in the bibliography [43,47], with a shift to lower δ values, due to the arrangement of potassium atoms in the synthesized compounds.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 89%
See 1 more Smart Citation
“…The obtained bands agree with the ones reported in the bibliography [43,47], with a shift to lower δ values, due to the arrangement of potassium atoms in the synthesized compounds.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 89%
“…The bands at 991 cm -1 and 980 cm -1 are assigned to symmetric and asymmetric stretching (ν W-O d ). Also, two weak bands are observed at 899 cm -1 (ν as W-O b -W) and 544 cm -1 (ν as W-O c -W) [43]. The stretching J o u r n a l P r e -p r o o f vibration of the W-O d bond presents a shift with respect to K 4 (SiW 12 O 40 ) due to vanadium incorporation [44].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 94%
“…Solutions were prepared in Milli-Q water. Na 1 K 3 [PW 11 V V O 40 ]•7H 2 O ([PW 11 V] 4– ), , K 5 [PW 11 V IV O 40 ]•14H 2 O ([PW 11 V] 5– ), K 4 [SiW 11 Mo VI O 40 ]•5H 2 O ([SiW 11 Mo] 4– ), K 5 [SiW 11 Mo V O 40 ]•12H 2 O ([SiW 11 Mo] 5– ), K 5 [SiW 11 V V O 40 ]•7H 2 O ([SiW 11 V] 5– ), , and Rb 5 K 1 [SiW 11 V IV O 40 ]•7H 2 O ([SiW 11 V] 6– ) , were synthesized and purified according to published procedures. The molybdenum-based phosphotungstates ([PW 11 Mo] 3/4– ) were also synthesized, but they were found to be unstable in aqueous solution, and therefore, they were not studied anymore.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of porous POM materials is also possible using appropriate inorganic counter cations, and such all-inorganic POM materials are expected to be highly stable under thermal and redox conditions. All-inorganic POMs can be roughly divided into two types: (A) those utilizing ionic bonds or hydrogen bonds between clusters and (B) those linking POMs with covalent bonds. For type A POMs, several examples of aluminum cluster-paired POMs are known. Kwon et al reported all-inorganic porous POMs composed of a cationic aluminum cluster, [Al 13 O 4 (OH) 24 (H 2 O) 12 ] 7+ ({Al 13 } 7+ ), with [Al­(OH) 6 Mo 6 O 18 ] 3– , or [V 2 W 4 O 19 ] 4– .…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported a material in which the [(P V O 4 )­V V 6 V IV 12 O 39 ] 3– unit was directly linked through V–O–V bonds . Three-dimensional (3D) Keggin-type POM frameworks with K + and Na + were reported using [SiMo 12 O 40 ] 4– , [SiVW 11 O 40 ] 5– , or [BW 12 O 40 ] 5– . In recent years, the combinations of POMs and cations, structures, and topologies have become greatly diversified.…”
Section: Introductionmentioning
confidence: 99%